PENERAPAN TEKNIK SENGKEDAN SECARA BERKELOMPOK UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS V SDN PAGENTAN 02 SINGOSARI DALAM MENENTUKAN KPK DAN FPB - Bambang Sukirnadi Kusbiantoro (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2016)
One of abstract mathematical and material related to everyday life is the determination of the KPK and the FPB. Based on observations in class V SDN Pagentan 2 shows that the students of class V SDN Pagentan 2 are less able to understand the concept of the KPK and the FPB. Students still confuse way in determining the KPK and the FPB. Students also have not been able to understand the concept of the KPK and the FPB properly so it can not resolve the issue properly. The determination of the KPK and the FPB with swales technique is one proposed solution to improve the learning process of the KPK and the FPB in class V SDN Pagentan 2 Singosari.This study uses a Class Action Research (CAR), which uses two cycles. Each cycle has stages namely planning (plan), action (action), observation (observation) and reflection (reflection). Subjects of the study were students of class V SDN Pagentan 2 Singosari totaling 32 students. The research instrument used is the syllabus, lesson plans, worksheets swales techniques, as well as formative test material KPK and FPB. Data were analyzed using the results of tests and observation. Mechanical swales in groups can help students of class V SDN Pagentan 2 in improving students' understanding of the concept of the KPK and the FPB material. The average value of understanding the concept of the cycle of 62.80 with 56.25% classical completeness. While the average value of understanding the concept in cycle two of 86.56 with classical completeness of 87.5%.